(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2015)
In 2011 the European Commission changed the definition and strategy for corporate social responsibility (CSR) with the creation of shared value as one core element of the new concept. In the same year Porter and Kramer published in the Harvard Business Review their approach of creating shared value (CSV) as core element of long-term business strategies. The starting point of both approaches is the societal legitimation of enterprises to do business. CSR respective CSV are evaluated to be a mean for reaching this legitimation and to further to gain back trust of the society that was lost during the financial crisis. This paper describes the two concepts and analyzes similarities and differences. From the overall aim and intention the EU concept has a wider focus and much higher requirements for enterprises. The European Commission assesses CSR as a measure for business to contribute to inclusive growth, employment and well-being of the society. Hence, companies have to take into account economic, social and environmental targets further include ethical, human rights and consumer concerns when developing their long-term business strategy. CSV of Porter and Kramer also goes beyond the pure business case of CSR because CSV also is defined as a long-term measure which has to be integrated systematically in the strategic core business of companies. The Commission see shareholder as just one common group of a company’s stakeholder and gives no preference to them. For Porter and Kramer the simultaneous creation of profit and societal value are decisive. Keywords: Shared value creation, corporate social responsibility, European CSR policy